American Teaching About Russia - Thompson, John; Black, Cyril E. (Indiana University Press, 1959)
American Teaching about Russia is a handbook for educators-the only one of its kind in existence-which not only examines the status of Russian and other non-Western studiesin American schools but presents many concrete suggestions for development of this crucial areas in the period of educational expansion that lies ahead. The authors discuss methods, teacher training, curriculum content, placement, and similar topics of practical import to our program at the graduate, undergraduate, and secondary levels. An over-all appraisal of the achievements, problems, and shortcomings of our present approach to non-Western studies gives balance and perspective to this pioneer work.